Integrating Financial Literacy into Community Banking Models: A Pathway to Empowerment - Faisal, Ijang (Yayasan Kreatif Indonesia Emas, 2024)
This study explores the critical role of integrating financial literacy into community banking models as a strategic pathway to economic empowerment, particularly in the underserved and unbanked areas of Indonesia. Despite the growth of formal financial institutions, a significant portion of the population remains excluded, with community banks and microfinance institutions serving as vital last-mile solutions. However, their long-term impact is often constrained by a lack of financial knowledge and poor behavioral habits among community members. This paper emphasizes how the strategic intersection of knowledge dissemination, financial inclusion, and sustained behavior change can create more robust and sustainable community banking ecosystems. Using a qualitative research methodology that synthesizes theoretical frameworks from behavioral economics, the capability approach, and social capital theory with empirical case studies from community banks in West Java and Central Sulawesi, the research identifies key drivers and barriers to effective integration. It proposes a scalable model where educational content is co-designed with community input, delivered through localized and hybrid channels, and leveraged by local champions. This approach aims not only to increase participation in formal banking but also to foster informed financial decision-making, ultimately contributing to a more resilient and empowered local economy.